High-yield Synthesis of Multiwalled Carbon Nanotube by Mechanothermal Method - Manafi, SA (Springer, 2009)
This study reports on the mechanothermal synthesis of multiwalled carbon nanotube (MWCNTs) from elemental graphite powder. Initially, high ultra-active graphite powder can be obtained by mechanical milling under argon atmosphere. Finally, the mechanical activation product is heat-treated at 1350°C for 2–4 h under argon gas flow. After heat-treatment, active graphite powders were successfully changed into MWCNTs with high purity. The XRD analyses showed that in the duration 150 h of milling, all the raw materials were changed to the desired materials. From the broadening of the diffraction lines in the XRD patterns, it was concluded that the graphite crystallites were nanosized, and raising the milling duration resulted in the fineness of the particles and the increase of the strain. The structure and morphology of MWCNTs were investigated using scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM). The yield of MWCNTs was estimated through SEM and TEM observations of the as-prepared samples was to be about 90%. Indeed, mechanothermal method is of interest for fundamental understanding and improvement of commercial synthesis of carbon nanotubes (CNTs). As a matter of fact, the method of mechanothermal guarantees the production of MWCNTs suitable for different applications.